Alarming Cargo: Regulation and Control at the UK Border - Downes, Robert James (Terrorism and political violence, 2021)
Programme CYCLAMEN was initiated to manage the risk of non-conventional terrorism in the United Kingdom following Al-Qaeda’s attacks against the United States in 2001. Under Programme CYCLAMEN, the UK developed a border monitoring capability to detect and deter the illicit cross-border movement of radiological and nuclear materials by malicious non-state actors. This paper examines the development of border monitoring technologies before and after 9/11 with a focus on Programme CYCLAMEN using two models of state response to terrorism. Under the Control Model, state agencies seek to manage the risk associated with terrorism through disruption of terrorist activities. Under the Regulatory Model, actions are conceptualised as safeguarding public health and safety from various sources of risk including terrorism. The Regulatory Model is found to be dominant before 9/11 but the Control Model dominated thereafter and Programme CYCLAMEN is best understood as emanating from the Control Model. However, earlier action under the Regulatory Model shaped later consideration of this particular border-based protective security measure. This paper explores this shaping process and concludes that the Regulatory Model is under-considered as a model of state response to terrorism.